2016
DOI: 10.1016/j.aop.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement thresholds for displaying the quantum nature of teleportation

Abstract: A protocol for transferring an unknown single qubit state evidences quantum features when the average fidelity of the outcomes is, in principle, greater than 2/3. We propose to use the probabilistic and unambiguous state extraction scheme as a mechanism to redistribute the fidelity in the outcome of the standard teleportation when the process is performed with an X−state as a noisy quantum channel. We show that the entanglement of the channel is necessary but not sufficient in order for the average fidelity f … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Besides, we consider that the measuring-basis can consist of non-Bell states. Additionally, we propose the so called unambiguous state extraction (USE) protocol [39][40][41][42] as the mechanism for implementing the local operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we consider that the measuring-basis can consist of non-Bell states. Additionally, we propose the so called unambiguous state extraction (USE) protocol [39][40][41][42] as the mechanism for implementing the local operations.…”
Section: Introductionmentioning
confidence: 99%
“…IV we summarize the principal results. Additionally, we included the Appendix A where we show that the unambiguous state extraction (USE) protocol [39][40][41][42] can be locally applied to extract an EPR state with optimal probability. In particular, we introduce an explicit joint unitary transformation, which allows to accomplish the main aim, additionally finding the optimal probability of success as a function of the initial concurrence [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…More general teleportation schemes considering these undesired aspects have been studied [9][10][11][12][13][14]. In particular, it has been found that the average fidelity of the deterministic teleportation becomes larger than 2/3 when the mixed state channel has non-classical features [13,[15][16][17]. Previous to apply the teleportation scheme, the mixed state channel can be manipulated via local filtering operations with the purpose of obtaining a state leading to the highest possible average teleportation fidelity, which has a Bell-diagonal normal form [16].…”
Section: Introductionmentioning
confidence: 99%
“…More general teleportation schemes considering these undesired aspects have been studied [9][10][11][12][13][14]. In particular, it has been found that the average fidelity of the deterministic teleportation becomes larger than 2/3 when the mixed state channel has non-classical features [13,[15][16][17]. Previous to apply the teleportation scheme, the mixed state channel can be manipulated via local filtering operations with the purpose of obtaining a state leading to the highest possible average teleportation fidelity, which has a Bell-diagonal normal form [16].…”
Section: Introductionmentioning
confidence: 99%